An evaluation method for power supply guarantee capability of multi-city interconnected power system based on security region - Zhihong Liu; Yunyao Chen; Yaoxia Du; Yang Luo (Frontiers in Energy Research)
In the context of global climate change, the multi-city interconnected power system offers the potential for low-carbon and efficient energy utilization, addressing the challenge of ensuring safety, stability, and reduced carbon emissions while meeting diverse demands. This study proposes a security region-based method to evaluate the power supply guarantee capability of such systems, employing a collaborative support framework to characterize the low-carbon feasible space of each city system. A multi-dimensional piecewise linear approximation method and model transformation were applied to construct a scheduling and transformation model for the provincial power grid. The proposed approach enhances power supply security, achieving a 7.21% reduction in system operating costs and a 24.7% decrease in carbon emissions. These findings highlight the effectiveness of the security region approach in balancing safety, efficiency, and environmental objectives, providing a scalable solution for interconnected power grids.